The family of man teenagers - British Broadcasting Corporation (London : BBC Enterprises, 1980)
The relationship between parents and teenagers, the generation gap, teenagers' relationship with each other, and the difficult transition froam child to adult
Copy available in DVD format
Keywords: Family